2022
DOI: 10.4143/crt.2021.205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness and Clinical Outcome of Everolimus Followed by CDK4/6 Inhibitors with the Opposite Treatment Sequence in Hormone Receptor-Positive, HER2-Negative Metastatic Breast Cancer

Abstract: In hormone receptor-positive, HER2-negative metastatic breast cancer (HR+ HER2-MBC), the mainstay treatment options include cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) and everolimus (EVE) in combination with endocrine treatment. This study aims to compare the outcomes of the following treatment sequences: CDK4/6i followed by EVE and EVE followed by CDK4/6i. Materials and MethodsData from HR+ HER2-MBC patients treated between Jan. 2014 and Nov. 2020 with both CDK4/6i and EVE were retrospectively analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Two studies compared the clinical effectiveness of different CDK4/6i treatment sequences (ESM) [ 36 , 37 ]. Basile et al reported that patients receiving CDK4/6i combined with chemotherapy in 1L followed by chemotherapy in 2L had significantly worse OS than those receiving CDK4/6i combined with ET in 1L followed by ET in 2L (hazard ratio: 6.95, p = 0.011) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared the clinical effectiveness of different CDK4/6i treatment sequences (ESM) [ 36 , 37 ]. Basile et al reported that patients receiving CDK4/6i combined with chemotherapy in 1L followed by chemotherapy in 2L had significantly worse OS than those receiving CDK4/6i combined with ET in 1L followed by ET in 2L (hazard ratio: 6.95, p = 0.011) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in overall survival between the two groups [77] . In contrast, Cook et al showed no influence of prior treatment with a CDK4/6 inhibitor on progression-free survival for patients treated with everolimus plus exemestane compared to patients without prior exposure (3.6 months vs. 4.2 months) [78] . In addition, they reported a numerical improvement in overall survival (15.6 months vs. 11.3 months) for patients previously treated with a CDK4/6 inhibitor [78] .…”
Section: Mtor Inhibitionmentioning
confidence: 92%
“…In contrast, Cook et al showed no influence of prior treatment with a CDK4/6 inhibitor on progression-free survival for patients treated with everolimus plus exemestane compared to patients without prior exposure (3.6 months vs. 4.2 months) [78] . In addition, they reported a numerical improvement in overall survival (15.6 months vs. 11.3 months) for patients previously treated with a CDK4/6 inhibitor [78] . The discussion of the efficacy of everolimus plus exemestane after treatment with a CDK4/6 inhibitor is accompanied by the discussion of the optimal treatment sequence.…”
Section: Mtor Inhibitionmentioning
confidence: 92%
“…This is exactly the same type of cancer that is also treated with palbociclib. In some studies, therapies with everolimus and palbociclib were used in sequence: when one of them failed, the other one was used in sequences [57][58][59]. In one trial, palbociclib was given first, followed by everolimus [57].…”
Section: Proposal: a Combination Of Mtor And Cdk4/6 Inhibitors To Mit...mentioning
confidence: 99%